2009
DOI: 10.1891/0886-6708.24.3.399
|View full text |Cite
|
Sign up to set email alerts
|

History of Abuse and Psychological Distress Symptoms Among Female Sex Workers in Two Mexico–U.S. Border Cities

Abstract: This study examined histories of past emotional, physical, and sexual abuse as correlates of current psychological distress using data from 916 female sex workers (FSWs) who were enrolled in a safersex behavioral intervention in Tijuana and Ciudad (Cd.) Juarez, Mexico. We hypothesized that histories of abuse would be associated with higher symptom levels of depression and somatization, and that social support would moderate the relationship. Nonparametric correlations and a series of hierarchical regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 40 publications
5
36
0
Order By: Relevance
“…25,26 Sex work and associated traumas may also lead to substance use. 30 Increasingly, prevention advocates recognize the need to consider the issues of past victimization, violence and trauma, and substance use in interventions for this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Sex work and associated traumas may also lead to substance use. 30 Increasingly, prevention advocates recognize the need to consider the issues of past victimization, violence and trauma, and substance use in interventions for this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…Violence was related to the occurrence of CMD, especially depression, 66,67,[72][73][74] post-traumatic stress disorder, 74 MUS, 66,67,[72][73][74] fibromyalgia, 69 and emotionally unstable (borderline) personality disorder. 70,71 C u l t u r a l f a c t o r s a n d c u l t u r e -b o u n d syndromes 31,81,83,86,88-94 The literature regarding CBS in LA describes a set of conditions that overlap with somatization phenomena in this region.…”
Section: -74mentioning
confidence: 99%
“…The prevalence of psychological distress among FSWs is well documented internationally (33-38). In 1998, Farley et al (39) suggested that psychological distress among sex workers should be treated as a health crisis just as important as the HIV epidemic.…”
Section: Introductionmentioning
confidence: 99%